Determinasi Keputusan Berkunjung Wisatawan dan Strategi Pengembangan Wisata Edukasi - Kurniawan, Irghi Ahmad; Annis Nurfitriana Nihayah (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the determinants of visit decisions and development strategies for educational tourism at Semarang Zoo. This study uses a quantitative and qualitative approach with a sample of 100 respondents. Data were analyzed using multiple linear regression analysis. The results show that tourist attraction has a positive but insignificant relationship with tourists' decisions to visit. Conversely, facilities and travel costs have a positive and significant relationship with the decision to visit. These findings indicate that adequate facilities and affordable travel costs are the main factors in encouraging tourist visits, while tourist attractions require more optimal management to increase visitor interest. This study recommends that the management of Semarang Zoo improve innovation in tourist attractions, maintain the quality of facilities, and ensure the affordability of travel costs to increase the number of tourist visits.